Number of J/ψ events at BESIII *Supported in part by National Key R&D Program of China (2020YFA0406300, 2020YFA0406400); National Natural Science Foundation of China (NSFC) (11625523, 11635010, 11735014, 11822506, 11835012, 11935015, 11935016, 11935018, 11961141012, 12022510, 12025502, 12035009, 12035013, 12061131003, 12075252); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1732263, U1832207); CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH040); 100 Talents Program of CAS; INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (758462); European Union Horizon 2020 research and innovation programme Marie Sklodowska-Curie grant agreement (894790); German Research Foundation DFG (443159800), Collaborative Research Center CRC 1044, FOR 2359, GRK 214; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey under Contract No. DPT2006K-120470; National Science and Technology fund; Olle Engkvist Foundation (200-0605); STFC (United Kingdom); The Knut and Alice Wallenberg Foundation (Sweden) (2016.0157); The Royal Society, UK (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0012069). (1st July 2022) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Ahmed, S.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, X. H. 旭红; Bai 白, Y. 羽; Bakina, O.; et al.
Abstract: Using inclusive decays of, a precise determination of the number of events collected with the BESIII detector was performed. For the two data sets taken in 2009 and 2012, the numbers of events were recalculated to be and, respectively; these numbers are in good agreement with the previous measurements. For the sample taken in 2017–2019, the number of events was determined to be . The total number of events collected with the BESIII detector was determined to be, where the uncertainty is dominated by systematic effects, and the statistical uncertainty is negligible.